Meningkatkan Pengetahuan Masyarakat Terkait Infeksi Saluran Pernapasan Akut (Ispa) Melalui Penyuluhan - Lestari, Katrina Feby; Syariah, Tata; Aulia, Rizky Nurwanda Nurul; Makmur, Atika Hi.; Barasandji, Asti Fattimah A.; Mahyudin, Nadia; Fidyah, Nurul; Pieronica, Adelia; Wijayanti, Nur Istiqomah Annisa; Rotiensulu, Desi Natalia; Kadafi, Moh. Ifan; Humairah, Nurul; Tebisi, Juwita Meldasari (Abdimas Indonesian Journal, 2025)
Introduction: Acute Respiratory Infection is a disease that attacks the upper or lower respiratory tract and is usually contagious. One way that can be done to reduce the incidence of Acute Respiratory Infection is to increase public knowledge. Knowledge can be increased through health education. Objective: To increase public knowledge regarding Acute Respiratory Infection. Method: Health education is used as a method in this community service activity accompanied by pre and post tests. Results: Before being given health education there were 60% who had good knowledge, 35% had sufficient knowledge, and 5% had less knowledge, whereas after being given health education there were 50% who had good knowledge and 50% who were sufficient. Conclusion: Health education can be used as an effort to increase public knowledge about Acute Respiratory Infection.